BENTUK HUBUNGAN MASYARAKAT (PUBLICITY) PONDOK PESANTREN ANDALUSIA KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - Nora Zulvianti; Asri Noviyanti (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
Promotion is one part of a series of marketing activities for a product. Promotion is an effort to introduce a product to potential buyers. Promotion has several components, one of which is public relations. Public relations carried out by the Andalusian Islamic Boarding School, Pauh Duo District, South Solok Regency are still not optimal. The purpose of this study was to describe the community relations carried out by the Andaluisa Islamic Boarding School, Pauh Duo District, South Solok Regency. This research is a field research. The method used is a qualitative method. This type of research is descriptive. The findings of this study are that the Andalusian Islamic Boarding School, Pauh Duo District, South Solok Regency has carried out promotions in the form of public relations.